Estudio de credibilidad de los comunicadores digitales en redes sociales - Litardo Landivar, Jorge Isaac (2020)
The general objective of this document is to determine the credibility study of digital communicators in social networks. To achieve this, two surveys were applied with different questions to users and communicators of digital media, resulting in that Facebook is the most common digital platform, that social media is a contribution to journalism as long as it is known to give a good handling, and that not everything that is published is true. In the theoretical support, the variables of the subject are defined, the types of social networks are mentioned, the advantages and disadvantages of social networks for digital communicators are highlighted. How should the profile of a communicator of these online media be, and their credibility is conceptualized. On the other hand, data collection techniques such as observation and surveys that helped to carry out the work were used. The types of research implemented were the bibliographic ones that, through theoretical support and qualitative research, the development of the research project was elaborated. At the end of the document, the conclusions and recommendations found throughout and at the end of the preparation of the work are reflected, taking into account the results, theoretical support and personal opinion of the author. All the investigation is supported with the annexes that prove the accomplishment of the same one.